Scholarly communication and matters of trust and authority: A comparative analysis of Malaysian and Chinese researchers - Abrizah, A.; Xu, Jie; Nicholas, David (Malaysian Journal of Library and Information Science, 2017)
The study is a follow up of CIBER’s exploratory research on Trust and Authority in Scholarly Communications conducted in 2012-2013, investigating Malaysia, a country currently on the ‘periphery’ of the scholarly endeavor and comparing with China, now stands 2nd globally to the USA in terms of scientific output. Over 500 Malaysian researchers were surveyed about the opinions on trustworthiness when it came to their scholarly use/reading, citing and publishing. A high proportion of respondents were affiliated to research-intensive universities, with the early career researchers and physical sciences being very well-represented. The attitudes and behaviours of Malaysian researchers were compared with an earlier study of more than 660 Chinese, the methods and questions of which were replicated from the CIBER study. Results indicate that the measures of establishing trust and authority in scholarly communication do not seem to have differed profoundly in Malaysia and China.